Inelastic interactions of 200 GeV and 300 GeV protons with emulsion nuclei. - Areti, V. H. (University of Ottawa (Canada), 1976)
Proton-nucleus interactions, in nuclear emulsion, at incident proton energies of 200 GeV and 300 GeV are studied. The emulsion stacks were exposed with the emulsion surface perpendicular to the beam direction. The results obtained are found to be compatible with those obtained, by scanning along the track of the incident proton, in the horizontally exposed stacks. The inelastic mean-free-path is essentially the same at the two energies: 33.4+/-2.6 cm at 200 GeV 34.6+/-1.8 cm at 300 GeV. The average number of black tracks and the average number of grey tracks are also observed to be the same at both energies: < Nb>=5.9+/-0.4, < N g>=1.7+/-0.2 at 200 GeV and < Nb>=6.1+/-0.3, < Ng>=1.7+/-0.1 at 300 GeV. The average number of shower particles, < ns>, increases from 13.4+/-0.6 at 200 GeV to 15.2+/-0.4 at 300 GeV. < ns> may be given by < n s>=1.85 s1/3, where s is the square of the C.M. energy of the nucleon-nucleon system. It is shown that the ratio of dispersion D to the averagae multiplicity in proton-nucleus collisions is independent of the target nucleus. It is also shown that the multiplicity distribution (in emulsion) obeys the KNO semi-inclusive scaling law in the energy range of 6.2 GeV to 300 GeV. The scaling function applied by Buras et al the proton-proton multiplicity distributions was used. It is argued that the proper quantity that gives the correct A dependence of the production of particles in proton-nucleus collisions is the ratio of created charges in proton-nucleus and proton-proton interactions. The predictions for the average multiplicity and the above mentioned ratio, from various models, are compared with the experimental values. The predictions of the models discussed agree reasonably well with the experimental results. The rapidity distribution provides a crucial test for the models considered. The models' prediction that there should be no difference between proton-nucleus and protonproton distributions, in the foreward region of the rapidity (in this case ln tan thetaL/2) plots is verified. It is concluded that with extensive data using various nuclear targets, it should be possible to eliminate some of the models since the models differ in the prediction of the boundary of the region where the excess number of particles (compared with proton-proton distribution at the same energy should appear.
Keywords: Physics, Nuclear.